Long-Term Gynecological Outcomes in Women with Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency. (25th August 2010) - Johannsen, T. H.; Ripa, C. P. L.; Carlsen, E.; Starup, J.; Nielsen, O. H.; Schwartz, M.; Drzewiecki, K. T.; Mortensen, E. L.; Main, K. M.
Abstract : Background . Our knowledge on long-term outcome in CAH remains incomplete. Methods . In a prospective study (33 CAH patients, 33 age-matched controls), reproductive outcomes, self-rating of genital appearance and function, and sexuality were correlated to degree of initial virilisation, genotype, and surgery. Results . Patients had larger median clitoral lengths (10.0 mm [range 2–30] versus 3.5 [2–8], P < .001 ), shorter vaginal length (121 mm [100–155] versus 128 [112–153], P = .12 ), lower uterine volumes (29.1 ml [7.5–56.7] versus 47.4 [15.9–177.5], P = .009 ), and higher ovarian volumes (4.4 ml [1.3–10.8] versus 2.8 [0.6–10.8], P = .09 ) than controls. Satisfaction with genital appearance was lower and negatively correlated to degree of initial virilisation (r s = ≤ − 0.39, P ≤ .05 ). More patients had never had intercourse (P = .001 ), and age at 1st intercourse was higher (18 yrs versus 16 yrs, P = .02 ). Conclusion . Despite overall acceptable cosmetic results, reproductive outcomes were suboptimal, supporting that multidisciplinary teams should be involved in adult follow up of CAH patients.